Dennett's philosophy : a comprehensive assessment - Ross, Don, 1962-; Brook, Andrew; Thompson, David, 1941- (Bradford book., 2000)
The influential philosopher Daniel Dennett is best known for his distinctive theory of mental content, his elucidation of how the complex components of mental processing seem to come together in the relatively coherent narratives that we tell ourselves about ourselves and in his vivid accounts of how to think about minds in their evolutionary setting. The essays in this collection step back to ask: Do the complex components of Dennett's work on intentionality, consciousness, evolution, and ethics themselves come together into a coherent philosophical system?The essays, which grew out of a conference attended by Dennett, consider evolution, intentionality, consciousness, ontology, and ethics and free will. Unusually, for a collection of this kind, the authors were able to take account of Dennett's comments on their views. In the concluding essay, "With a Little Help from My Friends," Dennett offers his own thoughts on the comprehensiveness of his philosophy. ContributorsAndrew Brook, Timothy Crowe, Daniel C. Dennett, Paul Dumouchel, Timothy Kenyon, Dan Lloyd, Ruth Garrett Millikan, T. Brian Mooney, Thomas Polger, David Rosenthal, Don Ross, William Seager, David Thompson, Christopher Viger